Critical Reflexivity and Positionality on the Scholar-Practitioner Continuum: Researching Women's Embodied Subjectivities in Sport - Fabiana Cristina Turelli; Alexandre Fernandez Vaz; David Kirk (MDPI AG, 2023)
The sports world has many prejudices that have been converted into common sense. Some relate to the idea of athletes being strong or pretty but endowed with little intelligence. There is another view, perhaps a little more accurate, around the reification of consciousness in the name of the automation and maximum outcome of the body. Both views are informed by Cartesian thinking, perpetuating the mind-body dichotomy. Such a dichotomy is spread in several other areas in our society, expressed as binaries. We meet a binary when conducting research as well, disembodying the researcher as someone who is neutral, objective, and highly rational, and someone who, in synthesis, performs good mental work, but who must not let feelings intrude. On the contrary, we argue that we are embodied beings who are often not able to (and maybe should not) become detached from previous experiences and knowledge when conducting research. Even though this can present itself as a challenge, we consider that a fluid non-binary positioning encompasses actions holistically and leads to tasks being performed on a continuum. The purpose of this paper is to explore the reflexive process embedded in carrying out a PhD project committed to studying the production of the embodied subjectivities of a group of women high-level athletes in karate. The researcher inserted in the researched environment was not a high-level athlete; however, she had several experiences competing at the amateur level in different countries and faced experiences that were, to some extent, similar to those of the elite athletes. She used her previous experiences as a karateka, researcher, and woman to inform her research-doing since the intersectional social issues faced by her and lived queer feelings motivated her research questions. She plunged into a process of self-reflection and counted on the guidance of the other authors to organise her learning in order to use it in her scholarship. That was, primarily, an experience of "practice" of subjectivity through examining others' production of subjectivity, besides strengthening a positionality that lacked self-confidence. Thus, we explore issues around the researcher-practitioner theoretical-practical continuum of research-doing, presenting a journey that became empowering.